Modulating the dynamics of Forster resonance energy transfer and singlet fission by variable molecular spacers - Zirzlmeier, Johannes; Lavarda, Giulia; Gotfredsen, Henrik; Papadopoulos, Ilias; Chen, Lan; Clark, Timothy; Tykwinski, Rik R.; Torres, Tomas; Guldi, Dirk Michael (Nanoscale, 2020)
In contrast to previous work, the synergy between panchromatic absorption and molecular singlet fission (SF) is exploited to optimize solar energy conversion through evaluation of the distance dependence of intramolecular Forster Resonance Energy Transfer (i-FRET) in a series of subphthalocyanines (SubPcs) linked to pentacene dimers (Pnc(2)s). To provide control over i-FRET, the molecular spacer rather than the energy donating SubPc is tailored in the corresponding SubPc-Pnc(2) conjugates in terms of length (i.e., the number of aryl units) and flexibility (i.e., presence or absence of a CH2 group). AM1-CIS calculations support the experiments, which underline the importance of the molecular spacer to impact not only the i-FRET dynamics, but also the dynamics of intramolecular singlet fission (i-SF). For example, an additional phenyl group slows down both i-FRET and i-SF by a factor of similar to 3.8 and similar to 1.6, respectively, by a quinone-like conjugation pattern that affords a pentacene acceptor orbital that is fairly delocalized over both pentacenes and the bridging phenyl.
CRIS-Team WoS Importer:2020-12-11